Portable electric canting pen with palm wax sticks: Efficiency, user satisfaction and cost analysis for batik fabric production - Sinthusarn, Apaporn; Sincharoenpokai, Somphon; Pengprom, Kartoon (Bulletin of Applied Sciences, 2025)
This research aimed to evaluate the efficiency, user satisfaction, and cost analysis of a portable electric canting pen used in conjunction with palm wax sticks in the batik fabric production process. This innovation, developed by the research team, was designed to address limitations in the traditional wax-drawing stage of batik making. The study began with the design of research methodology, identification of the population and target groups, selection of research instruments, experimental trials, data collection, followed by analytical discussions and conclusions. The research findings indicate that the portable electric canting pen and palm wax sticks demonstrated high efficiency in wax application on batik fabric, with overall suitability and feasibility rated at a high level. When compared to traditional canting tools, the electric version received the highest level of user preference. Although the initial field tests showed that the electric canting pen took slightly longer to operate, this was attributed to users’ unfamiliarity with the device and its temperature control system during the first use. The overall satisfaction score was at the highest level (x̅ = 4.25 + 0.65), equivalent to 85 percent. Cost and constraint analysis revealed that the innovation reduced energy consumption by up to 155 times, decreased material costs by over 36 percent, and shortened batik production time by approximately 40 percent. Additionally, it alleviated labor constraints, enhanced operational convenience and safety, and allowed for easy procurement of palm wax materials for stick production. This research outcome is expected to improve the safety and quality of life of batik artisans, elevate the national standard of batik production, and promote sustained and creative development of the craft sector.